2015
DOI: 10.1038/srep16895
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Regulation of Chromatin Architecture Instills a Mechanical Memory in Mesenchymal Stem Cells

Abstract: Mechanical cues direct the lineage commitment of mesenchymal stem cells (MSCs). In this study, we identified the operative molecular mechanisms through which dynamic tensile loading (DL) regulates changes in chromatin organization and nuclear mechanics in MSCs. Our data show that, in the absence of exogenous differentiation factors, short term DL elicits a rapid increase in chromatin condensation, mediated by acto-myosin based cellular contractility and the activity of the histone-lysine N-methyltransferase EZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
199
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(211 citation statements)
references
References 53 publications
10
199
2
Order By: Relevance
“…This increased calcium mobilization may itself impact lamin processing (Kalinowski et al, 2013), creating a feed-forward loop to ensure that the nucleus remains patent under conditions of high mechanical activity. We recently showed that ATP-purinergic signaling is a central modulator in the load-induced-chromatin condensation in MSCs, as is signaling thorough Smad proteins (Heo et al, 2015, 2016). Further, we have established that the giant isoform of nesprin-1 (a component of the LINC complex that mediates actin connectivity to the nucleus) is essential for mechanical force transfer to the nucleus and activation of the YAP/TAZ pathway in response to exogenous mechanical loading (Driscoll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This increased calcium mobilization may itself impact lamin processing (Kalinowski et al, 2013), creating a feed-forward loop to ensure that the nucleus remains patent under conditions of high mechanical activity. We recently showed that ATP-purinergic signaling is a central modulator in the load-induced-chromatin condensation in MSCs, as is signaling thorough Smad proteins (Heo et al, 2015, 2016). Further, we have established that the giant isoform of nesprin-1 (a component of the LINC complex that mediates actin connectivity to the nucleus) is essential for mechanical force transfer to the nucleus and activation of the YAP/TAZ pathway in response to exogenous mechanical loading (Driscoll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechanism by which a mechanical memory is imprinted onto a cell is by physically altering the chromatin state. Indeed, calcium signaling downstream of cyclic stretch triggers changes in chromatin organization, and is proposed to elicit a mechanical memory in response to environmental mechanics [36]. Of note, multiple rounds and not singular episodes of loading are required to achieve a memory in MSCs, thereby providing flexibility in the system for cells to transiently survey diverse environments without being irreversibly sent down a specific fate pathway.…”
Section: Tension At the Single Cell Levelmentioning
confidence: 99%
“…The authors identified ATP release and calcium signalling induced by mechanical stretch as the mediators of this condensation process. Following being subjected to stretch, it was also found that the cells retained a ‘mechanical memory’, whereby the cells exhibited higher amounts of chromatin condensation that persisted for longer times, when subjected to increasing numbers of loading events and strain levels, which may be a mechanism by which the MSCs sensitize themselves to future loading events [54]. Collectively, these studies emphasise just how far reaching the effects of mechanical stretch can be on MSC physiology and maintenance, and show how tensile loading can affect not only cellular differentiation, but also affect apoptosis, ROS, calcium oscillations and matrix mineralisation.…”
Section: Other Effects Brought About By Mechanical Strainmentioning
confidence: 99%